The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7863/ultra.33.5.769
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Rater Reliability and Measurement Error of Sonographic Muscle Architecture Assessments

Abstract: Sonographic examination of muscle architecture of the medial gastrocnemius has good to high reliability. In contrast to pennation angle measurements, length measurements can be improved by standardization of the probe position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
2
36
1
Order By: Relevance
“…Overall, the results of the present study suggest that reliable measures of MG architecture at rest can be attained using a combination of ultrasonography and image analysis. Although a recent study [ 16 ] found inter-rater reliability of MG architecture to be good-excellent (ICC = 0.77-0.90), it is recommended that a single rater both captures and analyzes MG ultrasound images due to the higher ICCs reported in the present study. Also, where possible, it is recommended that sonographic images of pennate skeletal muscle is recorded using a probe of sufficient proportions to allow for the capture of the entire fascicle length, given the previously reported underestimation [ 14 ] and greater within-image [ 11 ] and between-session [ 12 ] variability reported when using the linear extrapolation method.…”
Section: Discussionmentioning
confidence: 73%
“…Overall, the results of the present study suggest that reliable measures of MG architecture at rest can be attained using a combination of ultrasonography and image analysis. Although a recent study [ 16 ] found inter-rater reliability of MG architecture to be good-excellent (ICC = 0.77-0.90), it is recommended that a single rater both captures and analyzes MG ultrasound images due to the higher ICCs reported in the present study. Also, where possible, it is recommended that sonographic images of pennate skeletal muscle is recorded using a probe of sufficient proportions to allow for the capture of the entire fascicle length, given the previously reported underestimation [ 14 ] and greater within-image [ 11 ] and between-session [ 12 ] variability reported when using the linear extrapolation method.…”
Section: Discussionmentioning
confidence: 73%
“…Three images were taken at each site in a longitudinal plane, and then exported to Image J (National Institutes of health, Bethesda, MD, United States, version 1.8.0_112) for analysis. The average value from the three images were used for analysis (Aagaard et al, 2001); a methodology that has shown high absolute and relative reliability for architectural parameters being measured in this way (Ema et al, 2013b;König et al, 2014;Silva et al, 2018). All images were taken from the participants' dominant limb (defined as the leg with which they would kick a ball) by the same experienced sonographer.…”
Section: Ultrasound Assessmentmentioning
confidence: 99%
“…Reported estimates of reliability were good to high. [13][14][15][16][17][18][19][20][21] With the exception of a study reported by Thoirs and Englsh, 15 the reported intrarater correlation coefficients (ICC) among studies ranged between 0.90 and 0.99. Thoirs and Englsh 15 reported that high test-retest reliability was indicated in the lower extremity when subjects were measured in a standing position (ICC, 0.70-0.89; 95% confidence interval (CI), 0.79-0.94 for anterior thigh and 0.49-0.84 for posterior thigh, respectively).…”
Section: Validity and Reliability Of Mt Measurementsmentioning
confidence: 99%
“…Two studies 16,21 reported interrater reliability in the lower extremity muscles and the values demonstrated high reliability (ICC, 0.82 and 0.95). Furthermore, a study 19 investigated inter-machine reliability of different ultrasound machines and found that inter-machine reliability was considered excellent.…”
Section: Validity and Reliability Of Mt Measurementsmentioning
confidence: 99%